HTML5-based graphic image processing and collaborative drawing technology - Yinghua Liang (Systems and Soft Computing)
HTML5 technology has great technical advantages and influence on the graphical image processing function of mobile devices. The purpose of this study is to evaluate the performance of HTML5 graphics and image processing and co-rendering technologies and to verify the effectiveness and usefulness of these technologies, including the measurement of user experience and efficiency. The simulation analysis is carried out on MATLAB, and different image compression algorithms are used for comparison. The evaluation indexes include peak signal-to-noise ratio (PSNR) and structural similarity (SSIM). Comparing the two methods of Joint Image Expert Group (JPEG) and fractal Image Compressed file (IFS), the results showed that the proposed algorithm provided better PSNR and SSIM values than IFS, and provided higher PSNR and lower SSIM values than JPEG under the condition of increasing compression ratio, showing excellent image processing and compression efficiency. Then, the correlation loss, brightness distortion, contrast distortion, and color distortion of image processing are analyzed for the four real scenes of blur, illumination, cloud, and strong light. The results showed that compared with JPEG and IFS, the correlation loss of the proposed algorithm was 15.46, 16.25, 16.78, and 17.45, respectively. It had lower correlation loss, brightness distortion, contrast distortion, and color distortion, and showed better image processing effects. In general, the study found that the graphics and image processing and co-rendering technology based on HTML5 has high efficiency and effect in image processing and compression, especially in complex environments and conditions, such as fuzzy conditions, lighting conditions, cloudy weather, and strong light conditions, showing excellent performance and adaptability. This discovery provides important evidence for its practical application in many fields such as computer vision, medical imaging, and remote sensing image analysis, and helps to promote the development and innovation of image processing technology in these fields to meet the increasing practical needs.